Minority shareholders : (Butterworths, 2008)
An invaluable addition to a relatively unpopulated area of the law...it is very difficult to find fault with this work. ..One can only echo the words which find expression in the present Foreword that this work has become 'an essential working tool' for those operating in this area. David Marks, International Company and Commercial Law Review